Pengaruh Citra Merek, Kualitas Produk dan Customer Value terhadap Keputusan Pembelian Sampo Clear : (Studi Kasus pada Mahasiswa UMUS) - Citra Mega Suara; Siti Anah Fadhillah; Hendri Sucipto; Akbar NPD Wahana; Amelia Sholeha (BADAN PENERBIT STIEPARI PRESS, 2023)
This study aims to analyze the influence of brand image, product quality, and customer value on the purchase decision of Clear Shampoo among Muhadi Setiabudi University students. The study population was 520 students, a sample of 84 respondents was selected by a simple random sampling method. Survey instruments in the form of questionnaires are used to collect the necessary data. Multiple regression analysis will be used to evaluate the influence between the independent variable (brand image, product quality, and customer value) and the dependent variable (purchase decision). This research is expected to provide a deeper understanding of the preferences and factors that influence students in choosing Clear Shampoo as their hair care product. The results showed that all variables and questions in the questionnaire have been proven valid and reliable based on those made on the purchase decision of Clear Shampoo products in students. The implications of these findings are expected to provide valuable insights for manufacturers and marketers in improving their marketing strategies, especially in understanding how brand image, product quality, and customer value influence buying behavior in this particular target market.